Human Papillomavirus Antibody Levels Following Vaccination or Natural Infection Among Young Men Who Have Sex With Men . (31st December 2021) - Chow, Eric P F; Fairley, Christopher K; Zou, Huachun; Wigan, Rebecca; Garland, Suzanne M; Cornall, Alyssa M; Atchison, Steph; Tabrizi, Sepehr N; Chen, Marcus Y
Abstract: Background: Australia introduced a school-based gender-neutral human papillomavirus (HPV) vaccination program for girls and boys aged 12–13 years in 2013. We examined HPV type–specific antibody levels in unvaccinated young men who have sex with men (MSM) with natural infection and compared these with levels in those vaccinated against HPV. Methods: Serum specimens at baseline were collected from MSM aged 16–20 years in the HYPER1 (Human Papillomavirus in Young People Epidemiological Research) and HYPER2 studies, conducted in 2010–2013 and 2017–2019, respectively. Merck's 4-plex HPV competitive Luminex Immunoassay was used to quantify HPV6-, HPV11-, HPV16-, and HPV18-specific antibodies. We compared antibody levels for each HPV genotype between unvaccinated men (HYPER1) and vaccinated men (HYPER2) using the Mann-Whitney U test. Results: There were 200 unvaccinated men and 127 vaccinated men included in the analysis. Median antibody levels among vaccinated men were significantly higher than levels among unvaccinated men for HPV6 (223 milli-Merck units per milliliter [mMU/mL] vs 48 mMU/mL, P < .0001), HPV11 (163 mMU/mL vs 21 mMU/mL, P < .0001), HPV16 (888 mMU/mL vs 72 mMU/mL, P < .0001), and HPV18 (161 mMU/mL vs 20 mMU/mL, P < .0001). Antibody levels did not change over time for up to 66 months for all 4 genotypes among vaccinated men. Conclusions: Among young MSM vaccinated with the quadrivalent HPV vaccine, antibody levels for HPV6, HPV11, HPV16, and HPV18 were significantly higher than those in unvaccinated MSM following natural infection. Antibody levels following vaccination appeared to remain stable over time. Clinical Trials Registration: NCT01422356 for HYPER1 and NCT03000933 for HYPER2. Abstract : Antibody levels are substantially higher following vaccination against human papillomavirus types 6, 11, 16, and 18 compared with natural infection among adolescent gay and bisexual men aged 16–20 years.